Outcome of patients with advanced lung adenocarcinoma treated with first-line epidermal growth factor receptor tyrosine kinase inhibitors versus cytotoxic chemotherapy - Chai, Chee She (Universiti of Malaya, 2015)
Background: There is no published data on the response and survival of Malaysian patients with locally advanced or metastatic adenocarcinoma of the lung with and without epidermal growth factor receptor (EGFR) mutations treated with EGFRtyrosine kinase inhibitors (TKIs) or cytotoxic chemotherapy. Objectives: This study aimed to examine (1) the progression-free survival (PFS) with first-line treatment, (2) the overall survival (OS) from the start of first-line treatment, and (3) the objective response rate (ORR) and disease control rate (DCR) with first-line treatment in Malaysian patients with locally advanced or metastatic adenocarcinoma of the lung treated with EGFR-TKI versus cytotoxic chemotherapy. Patients and Methods: A retrospective cohort observational study of patients with locally advanced or metastatic adenoc,¥"cinoma of the lung and known EGFR mutation status treated in UMMC and UMSC during a 4-year period from 1 st August 2010 to 31 th July 2014. Results: Of a total of 341 patients, 150 (44%) had tumours harbouring EGFR mutations. For patients with EGFR mutation-positive tumours, the median PFS (6.93 months) for th'ose treated with first-line EGFE,-TKI (n =98) was significantly better than the median PFS (2.23 months) for those treated with first-line cytotoxic chemotherapy (n = 19) (hazard ratio, 0.50; 95% CI, 0.29 -0.84; P =0.010). This was particularly true for those with exon 19 deletion mutation [median PFS of 7.00 months versus median PFS of 1.57 months; (hazard ratio 0.30; 95% CI, 0.14 -0.63; P =0.001)]. 1II For patients with EGFR mutation-positive tumours, the median OS was similar irrespective of whether the patients received first-line EGFR-TKI or first-line cytotoxic chemotherapy [10.40 months versus 9.63 months (hazard ratio, 0.92; 95% CI, 0.49 1.73; P =0.797 ] but significantly better than BSC (2.23 months). The ORR to EGFRTKI and cytotoxic chemotherapy was 42.9% and 10.5%, respectively (odds ratio, 6.38; 95% CI, 1.40 -39.11; P = 0.017). The DCR with EGFR-TKI and cytotoxic chemotherapy was 79.6% and 36.8%%, respectively (odds ratio, 6.69; 95% CI, 2.33 19.19; P< 0.001). For patients with EGFR mutation-negative tumours, the median PFS (2.93 months) for those treated with first-line cytotoxic chemotherapy (n =85) was better than that (1.03 months) for those patients treated with first-line EGFR-TKI (n =16) (hazard ratio, 0.44; 95% CI, 0.25 -0.77; P =0.004). The median OS (l0.43 months) for those treated with first-line cytotoxic chemotherapy was (ar better than median OS (1.07 months) for those treated with first-line EGFR-TKI (hazard ratio, 0.24; 95% CI, 0.l2 -0.77; p < 0.001) or BSC [3.33 months, (hazard ratio, 0.41; 95% CI, 0.87 -1.58; P < 0.001)]. The ORR and DCR for first-line chemotherapy group was 16.5% and 51.8% respectively. None of these patients responded or had disease stabilisation with first-line EGFR-TKI treatment. Conclusions: This study showed the superiority of first-line EGFR-TKI over cytotoxic chemotherapy in patients with EGFR mutation-positive locally advanced or metastatic lung adenocarcinoma in tenns of PFS, ORR and DCR. In patients with EGFR mutationnegative tumours, first-line cytotoxic chemotherapy conferred PFS, OS, ORR and DCR benefits.